SCREENING OF MAIZE GENOTYPES AGAINST NORTHERN CORN LEAF BLIGHT - R. P. SRIVASTAVA, RAJESH SINGH; V. P. MANI; R. S. KHANDELWAL; LEKHA RAM (The Bioscan, 2014)
A study was carried out, involving 118 maize genotypes to identify, the new sources of resistance to ‘Northern Corn Leaf Blight’ under artificial epiphytotic condition at three locations viz, Almora, Nagenahalli and Varanasi for 12 years (1999-2011) with the help of three experiments. All the three Experiments included separates set of genotypes except 13 inbreds, (CM 145, CM 141, V336, V341, V348, CM145, V273, V342, V346, V338, V335, CM126 and CM212) which were common in II nd and IIIrd Experiments. The present study has helped in the identification of 26 resistant, 56 moderately resistant, 26 susceptible and 10 highly susceptible maize genotypes. Thirteen lines viz. V53, V334, V335, V336, V338, V339, V 341, V 345, V346, V 350, CM 104, CM118, CM 145 showed high level of resistance, where as inbred lines viz, V 25,V128, CM 126, CM 127, CM 212 and CM 202 showed high level of susceptibility as they scored about 3.5 disease score across the environment. The maize inbred lines CM 145, V 338 and V 336 expressed high level resistance in all three environments. It was also observed that average disease incidence was high in Mandya then Almora and Varanasi thus indicating that isolates of Exserohilum turcicum was more virulent at Mandya than rest of two environments.